Highlights of the society for immunotherapy of cancer (SITC) 27th annual meeting. Issue 1 (29th May 2013) - Stroncek, David F; Melief, Cornelis JM; Castiello, Luciano; Cesano, Alessandra; Cheever, Martin A; Civini, Sara; Comin-Anduix, Begonya; Gajewski, Thomas F; Greenberg, Philip D; Kalinski, Pawel; Kaufman, Howard L; Kershaw, Michael H; et al.
Abstract : The 27 th annual meeting of the Society for Immunotherapy of Cancer (SITC) was held on October 26–28, 2012 in North Bethesda, Maryland and the highlights of the meeting are summarized. The topics covered at this meeting included advances in cancer treatment using adoptive cell therapy (ACT), oncolytic viruses, dendritic cells (DCs), immune check point modulators and combination therapies. Advances in immune editing of cancer, immune modulation by cancer and the tumor microenvironment were also discussed as were advances in single cell analysis and the manufacture and potency testing of tumor infiltrating lymphocytes (TIL).